Unveiling paradoxes: navigating SMEs readiness in the post-pandemic normality - Rafael Castro; António Carrizo Moreira (Cogent Business & Management, 2024)
This paper centers on the challenges posed by the pandemic crisis, examining the crucial organizational and strategic alignments, as well as the inherent paradoxes that are pivotal in nurturing competitiveness within the changed post-pandemic business landscape for small and medium-sized firms (SMEs). Encompassing nearly 90% of all global businesses, SMEs have a central role in driving social advance, fostering entrepreneurship, innovation, and facilitating sustainable economic development within their communities. As the recent COVID-19 pandemic crisis conveyed demanding challenges for businesses, understanding its complete impact requires a thorough appreciation of the adaptive measures and organizational changes in the new post-crisis landscape. To this end, we have conducted a systematic literature review by examining 88 published articles, proposing a tri-dimensional categorization of SME practices and behaviors based on the existing body of knowledge. The study highlights the inherent challenges erupted from the pandemic driven VUCA environment, stressing the importance of adaptability and innovation within SMEs. Effective leadership and adaptability are deemed vital for steering SMEs through external contingencies, as well as embracing digitalization, technology advancements, and governmental support. Nonetheless, further research is warranted to grasp SMEs adaptability on the post-pandemic normality, urging policymakers to prioritize innovation, networking, and international expansion.
Keywords: 650; SMEs; crisis; post-pandemic; VUCA; systematic literature review; paradoxes